Disappearance of the Polar Cap Ionosphere During Geomagnetic Storm on 11 May 2019. Issue 6 (2nd June 2022) - Kwon, H.‐J.; Kim, K.‐H.; Jee, G.; Seon, J.; Lee, C.; Ham, Y.‐B.; Hong, J.; Kim, E.; Bullett, T.; Auster, H.‐U.; Magnes, W.; Kraft, S.
Abstract: Multi‐instrument data from Jang Bogo Station (JBS) in Antarctica were utilized to study ionospheric responses to the 11 May 2019 moderate geomagnetic storm. These include Vertical Incident Pulsed Ionospheric Radar (VIPIR)/Dynasonde, Fabry‐Perot Interferometer (FPI), GPS vertical total electron content (vTEC), and magnetometer. The VIPIR/Dynasonde observed long‐lasting (>11 hr) severe depletion of the electron density in the F‐region ionosphere over JBS. During the depletion interval, GPS TEC also correspondingly decreased, FPI neutral temperature was significantly enhanced, and the polar magnetic field variations showed positive and negative excursions in the Y (east) and Z (vertical) components, respectively. GK‐2 A satellite, located ∼2.5 hr west of JBS, observed negative magnetic field perturbations in the azimuthal BD component at geosynchronous orbit during the depletion of ionospheric plasma. Such a BD perturbation at geosynchronous orbit is due to the field‐aligned currents flowing out of the ionosphere. From these observations we suggest that transpolar ionospheric currents connected to the field‐aligned currents flowing on a substorm wedge‐shaped circuit act as a source of polar atmospheric heating during the moderate geomagnetic storm interval and that elevated heavy molecular gases (O2 and N2 ) by atmospheric heating contribute to the electron density depletion via increased recombination rate. Plain Language Summary: Geomagnetic storms considerably influence the high‐latitude ionosphere in its density distributions as well as dynamics. In the present paper, we report results of multi‐instruments observations of the stom‐time ionospheric changes with simultaneously observed thermospheric anc magnetospheric changes. The Vertical Incident Pulsed Ionospheric Radar/Dynasonde and total electron contents measured by ground GPS receiver observed depletion of the ionospheric electron density. We confirmed from model results that the depletion was caused by the upwelling atmospheric molecular gases. The heated neutral atmosphere was also confirmed by the observations for the themosphere from a Fabry‐Perot interferometer. The current system is a key process to enhanced the lower atmospheric temperature. During the depletion interval, the magnetic field on the ground showed significant variations. The geosynchronous satellite also observed negative fluctuations in the azimuthal component at around Jang Bogo Station, which corresponds to the fluctuation of the ground magnetic field. Such fluctuations at geosynchronous orbit are strongly related with field‐aligned current that are part of a current system associated with substorm. These observations support that field‐aligned current plays as a source of polar ionospheric heating during the moderate geomagnetic storm. Key Points: The disappearance of the F‐region ionosphere was observed during storm in the polar cap region The disappearance is associated with the atmospheric upwelling and resulting enhancement of the recombination The polar cap ionosphere can be significantly affected by substorm‐induced field‐aligned currents